DAMPAK PUTUSAN PENGADILAN TERHADAP SANGSI PADA ANAK PELAKU PERUNDUNGAN DALAM INTENSITAS PERILAKU VERBAL ( SUATU TINJAUAN UNDANG- UNDANG NOMER 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK) - Heru Ismaya; Rika Jazilatul Kholidah (Sebelas Maret University, 2026)
Bullying can be interpreted as a form of structured violence carried out with the aim of intimidating and maintaining dominance by a particular individual or group over a stronger entity. The court, as a legal institution, functions as an enforcement agency. Children are part of the younger generation and are a human resource that plays a strategic role in the future of the nation's ongoing struggle. The purpose of this study is to describe the deterrent effect of sanctions imposed on perpetrators of bullying in terms of the intensity of verbal behavior. The punishment for perpetrators of bullying according to Article 76 C of Law Number 35 of 2014 are as follows;